2017
DOI: 10.1016/j.jaad.2017.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Risk of malignancy with systemic psoriasis treatment in the Psoriasis Longitudinal Assessment Registry

Abstract: Long-term (≥12 months) treatment with a TNF-α inhibitor, but not methotrexate and ustekinumab, may increase risk for malignancy in patients with psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
114
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(124 citation statements)
references
References 28 publications
2
114
0
8
Order By: Relevance
“…TNF antagonists have been associated with increased risk of serious bacterial, viral and fungal infections in patients with psoriasis, including active tuberculosis and reactivation of latent tuberculosis infection . The data on malignancy risk with long‐term exposure to TNF antagonists are conflicting, with some studies and recent registry data suggesting a potential increased risk . Rare cases of new onset or exacerbation of demyelinating disorders have also been reported during treatment with TNF antagonists…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TNF antagonists have been associated with increased risk of serious bacterial, viral and fungal infections in patients with psoriasis, including active tuberculosis and reactivation of latent tuberculosis infection . The data on malignancy risk with long‐term exposure to TNF antagonists are conflicting, with some studies and recent registry data suggesting a potential increased risk . Rare cases of new onset or exacerbation of demyelinating disorders have also been reported during treatment with TNF antagonists…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] The data on malignancy risk with long-term exposure to TNF antagonists are conflicting, with some studies and recent registry data suggesting a potential increased risk. [5][6][7][8]10 Rare cases of new onset or exacerbation of demyelinating disorders have also been reported during treatment with TNF antagonists. [5][6][7][8] As understanding of psoriasis disease mechanisms has advanced, more targeted therapies have become available with the potential for improved safety and tolerability.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the fact that patients with a history of malignancy are usually excluded from clinical trials, data on the effect of a treatment with biologics on a possible tumor recurrence are rather limited . Although long‐term exposure (≥12 months) to TNF inhibitors may be generally associated with a higher risk of malignancy, such as lymphomas and nonmelanocytic skin cancer (NMSC), there are only limited large scale data on the aspect of tumor recurrence under these agents . A recent Swedish population‐based study on 467 patients with a history of solid cancer and rheumatoid arthritis (RA), that were treated with TNF inhibitors, showed no increased risk for cancer recurrence in these patients, although clinically meaningful risk increases could not be ruled out completely .…”
Section: Resultsmentioning
confidence: 99%
“…17 A second analysis of PSOLAR (n=12,090) suggested that treatment with an anti-TNF agent for 12 months or longer (but not shorter term exposure) may be associated with an increased risk of malignancy compared with non-treatment; neither ustekinumab nor methotrexate were associated with an increased risk. 18 An analysis of a US claims database of 42,981 patients found that infection was the most frequent adverse event with psoriasis treatments and this was less common with ustekinumab, adalimumab and etanercept than with conventional systemic and topical therapy. 19 Adalimumab was associated with a significantly lower risk of malignancy.…”
Section: An Analysis Of Rates Of Serious Infection Among Patients On mentioning
confidence: 99%